2019
DOI: 10.1155/2019/4946580
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and TGF-β1/Smads Signaling Are Involved in Rosa roxburghii Fruit Extract Alleviating Renal Fibrosis

Abstract: Fibrosis is involved in the pathogenesis of kidney diseases. We previously discovered that Rosa roxburghii fruit (Cili) possesses antifibrosis property in chronic renal disease, but the mechanisms are unknown. We hypothesized that Cili might prevent fibrosis development through mediating TGF-β/Smads signaling, which is known to be involved in renal fibrosis. This study aimed to confirm the effects of freeze-dried Cili powder in a rat model of unilateral ureteral obstruction (UUO) and examine TGF-β/Smads signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Mechanically, RSJ inhibited TGF-β1-induced Smad2/3 phosphorylation, and prevented EMT and fibroblast differentiation to reduce extracellular matrix and collagen deposition, thereby alleviating bleomycin-induced pulmonary fibrosis. The previous study also showed that Rosa roxburghii Tratt mitigated renal fibrosis by inhibiting the TGF-β1/Smads signaling pathway, 13 suggesting a potential protective role of RS or Rosa roxburghii Tratt in fibrosis.…”
Section: Food and Function Papermentioning
confidence: 87%
See 1 more Smart Citation
“…Mechanically, RSJ inhibited TGF-β1-induced Smad2/3 phosphorylation, and prevented EMT and fibroblast differentiation to reduce extracellular matrix and collagen deposition, thereby alleviating bleomycin-induced pulmonary fibrosis. The previous study also showed that Rosa roxburghii Tratt mitigated renal fibrosis by inhibiting the TGF-β1/Smads signaling pathway, 13 suggesting a potential protective role of RS or Rosa roxburghii Tratt in fibrosis.…”
Section: Food and Function Papermentioning
confidence: 87%
“…11,12 Its alpha-glucosidase inhibitory activity has been well described, 10 indicating that Rosa roxburghii Tratt has high nutritive value. In preclinical studies, Rosa roxburghii Tratt freeze-dried powder ameliorated renal fibrosis by regulating the TGF-β1/Smad signaling pathway, 13 suggesting that Rosa roxburghii Tratt has potential health benefits for pulmonary fibrosis. Rose sterilis (RS) is a new variety of Rosa roxburghii Tratt, and its production has already reached 100 000 tons per year.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, a growing number of scientific studies have demonstrated that RRF presents antioxidant, hypoglycemic, hypolipidemic, radioprotection, immunoregulation, anticancer, aging retarding, and antifibrosis activities. [5][6][7][8][9][10][11] Natural polysaccharides, being a large class of macromolecular compounds, have attracted extensive attention because of their low toxicity and excellent biological activities. Several natural active polysaccharides have been used in functional foods and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, a growing number of scientific studies have demonstrated that RRF presents antioxidant, hypoglycemic, hypolipidemic, radioprotection, immunoregulation, anticancer, aging retarding, and anti-fibrosis activities. 5–11…”
Section: Introductionmentioning
confidence: 99%
“…Smad3 protein can directly bind to the promoter region of collagen to up-regulate the expression of collagen and promote the process of renal fibrosis. 14,15 Oxidative stress injury is the basis of EMT, 16 smad3 protein reduces fibrosis and ECM deposition by inhibiting oxidative stress. 17,18 Thus, renal fibrosis is the most important feature of renal pathology of DN, which was related with smad3-mediated fibrosis and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%